La neuroeducación en el aprendizaje significativo en Educación Inicial I, del Centro Infantil Mundo de Ilusiones Guayas en el período lectivo 2020 - 2021. - Defaz Gallardo, Leslye Stefania (2021)
Neuroeducation studies the neural bases of learning, responsible for attention, motivation, memory, emotions and many other brain functions that should be stimulated and strengthened by teachers at all levels, which is why this research was born with the objective of strengthening meaningful learning in early education through neuroeducation in the Child Development Center Mundo de Ilusiones Guayas, in the school year, 2020 - 2021, The methodology used for the characteristics of the research was quantitative, it was based on the deductive scientific method, because it was based on existing theories, it is also descriptive, bibliographic and field, as techniques and instruments for data collection was used the survey that was applied to teachers and parents through the questionnaire, observation through the observation sheet that was applied to children. At the end of the diagnosis, it is concluded that in the age of 2 to 3 years it is important to strengthen the integral child development, through strategies for gross motor skills, so the proposal of this research was "Neuroeducation Strategies "Play and movement", strengthening meaningful learning in children of Sublevel Initial I, of the Children's Center "World of Illusions Guayas". Directed to early childhood education teachers who were socialized through theoretical and practical workshops, the teachers at the end of the socialization stated that the strategies used in the proposal and its application with the infants has allowed to generate significant learning of children on gross motor skills and recognized the importance of applying neuroeducation exercises for the inhibition of children, the results of the validation of experts and users was excellent having a regional and national impact, It is concluded that it was enriching to integrate the entire educational community in the process of teaching and learning of children, since the experts and users with their great scientific and educational contribution contributed to the proposal and its application to reach important and positive results, the director, teachers, parents contributed to the integral development of children, being all the beneficiaries of the project, building an environment of quality and warmth inside and outside the Children's Center.